Predicting Academic Emotions based on Spiritual Well-being and Life Satisfaction in Students of Shahrekord Girls' Technical and Vocational School - Ataei, Zahra (2021)
The aim of this study was to predict the academic emotions based on spiritual well-being and life satisfaction in students of Shahrekord Girls' Technical and Vocational School. This was a descriptive correlational study. The study population consisted of all students of Shahrekord Girls' Technical and Vocational School in the 2018-2019 school year. A total of 210 students were selected by the stratified random sampling. The data were collected using the achievement emotions questionnaire (AEQ) (Pekrun, 2005), the spiritual well-being (SWB) scale (Paloutzian and Ellison, 1983) and The Satisfaction With Life Scale (SWLS) (Diener, 1985). Statistical methods and multivariate regression analysis were applied to analyze the data. The results showed that spiritual well-being could predict the academic emotions like pride (β = 20%) and life satisfaction could predict the academic emotions such as enjoyment (β = 26%), anxiety (β = 24%), anger (β = 20%), hopelessness (Β = 31%) and boredom (β = 41%).